Asia - an Attractive Region for Offshoring? - Stawicka, Magdalena Kinga (Azja - atrakcyjny region dla offshoringu?, 2010)
Offshoring is a process consisting in moving an enterprise's production or services beyond its motherland. Recently it has been observed that this phenomenon has been growing and covering new fields of business activity. Asian states are the most frequently selected localizations for such a type of undertakings and India, China and Malaysia have been leaders for many years. Nevertheless, it is significant that such states are trusted simple services provision, e.g. call centre, while advanced services are provided in more developed economies. The goal of this paper is to show the offshoring phenomena in Asian states with use of generally-available statistical data and rankings provided by international institutes. An effect of his analysis will be specification of factors having an impact on this region's investment attractiveness.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 181-190
Keywords: Asia; BPO; offshoring